A GUIDE FOR UPDATING THE PAWNEE MENTAL HEALTH SERVICES WEBSITE - Jibowu, Morgan (My University, 2019)
Pawnee Mental Health Services’ website provided limited information to the people whom it targeted – consumers, potential donors, and healthcare providers. During my 240-hour internship, I reviewed a number of community mental health center websites, and I identified specific website features that would be directly beneficial to an upgrade of the Pawnee Mental Health Services websites. I created PowerPoint slides to update content that the management staff could then use to create a website. In addition, I created PowerPoint slides for use by the website designer to create pages and modules. Finally, I created a suicide prevention brochure to address an important un-met need. During the internship, I attended Community Mental Health Center Advocacy Day, furthering my public health networking experience.
Keywords: public health; website